Fluoride exchange by glass-ionomer dental cements and its clinical effects: a review - John W. Nicholson; Sharanbir K. Sidhu; Beata Czarnecka (Medical Journals Sweden, 2023)
AbstractThe topic of fluoride release and uptake by glass-ionomer (glass polyalkenoate) dental cements is reviewed. The study was based on a literature search carried out using PubMed. The main key words used were glass-ionomer and fluoride, and further refinements were made by adding the keywords anti-microbial, anti-caries and remineralization. Papers were selected from the initial search, which concentrated on fundamental aspects of fluoride release, including kinetics and the influence of the cement composition, and resulting clinical performance against caries. Other relevant papers were cited where they added useful and relevant data. From these published papers, it was possible to explain the detailed mechanism of fluoride release by glass-ionomer cements and also its uptake. Fluoride release has been shown to be a two-step process. In neutral solutions, the steps can be divided into early wash-out and long-term diffusion. In acid conditions, the early wash-out remains, though with greater amounts of fluoride released, and the long-term release becomes one of slow dissolution. The effect of fluoride on the viability of oral micro-organisms has been described, and glass-ionomers have been shown to release sufficient fluoride to reduce the size and viability of adjacent populations of oral bacteria. The effect of low levels of fluoride on the remineralization of tooth tissue has been considered. Levels needed to increase remineralization are much lower than those needed to adversely affect oral bacteria, from which we conclude that glass-ionomers release sufficient fluoride to promote remineralization. Despite this, there remains uncertainty about their overall contribution to sound oral health, given the widespread use of other sources of fluoride, such as toothpastes.